Euptox A Induces G1 Arrest and Autophagy via p38 MAPK- and PI3K/Akt/mTOR-Mediated Pathways in Mouse Splenocytes. (September 2017) - Mo, Quan; Hu, Liwen; Weng, Jiahua; Zhang, Yong; Zhou, Yancheng; Xu, Ruiguang; Zuo, Zhicai; Deng, Junliang; Ren, Zhihua; Zhong, Zhijun; Peng, Guangneng; Nong, Xiang; et al.
Euptox A (9-oxo-10, 11-dehydroageraphorone), the main toxin isolated from Eupatorium adenophorum, is known to induce immunotoxicity in animals. However, the precise mechanism underlying the effects of Euptox A on splenocytes is unclear. Here, we aimed to investigate the molecular mechanisms underlying the effect of Euptox A in mouse spleens after its intragastric administration and found that Euptox A exhibits proautophagic effects in splenocytes. Euptox A markedly arrested the splenocytes in the G0/G1 phase, which was accompanied by inhibition of the expression of the positive regulators CDK4, CDK2, cyclin D1, PCNA, and E2F1, and promotion of the expression of the negative regulators p53, p21 Waf1/Cip1, p27 Kip1, and Chk1. We also found that Euptox A did not markedly induce splenocyte apoptosis, but induced autophagy while increasing the subcellular localization of punctate LC3, ratio of LC3-II/LC3-I, and Beclin 1 levels, and decreasing p62 levels. Euptox A also significantly inhibited p-PI3K, p-p38 MAPK, p-Akt, and p-mTOR expression, but increased PTEN and p-AMPK expression. These results indicated that Euptox A induced splenocyte autophagy by inhibiting the PI3K/Akt/mTOR pathway, suppressing p38 MAPK expression, and activating AMPK. These findings provide new insights into the mechanisms involved in spleen toxicity caused by Euptox A in mice.